UV irradiation to mouse skin decreases hippocampal neurogenesis and synaptic protein expression via HPA axis activation. Issue 1 (December 2017) - Han, Mira; Ban, Jae-Jun; Bae, Jung-Soo; Shin, Chang-Yup; Lee, Dong Hun; Chung, Jin Ho
Abstract The skin senses external environment, including ultraviolet light (UV). Hippocampus is a brain region that is responsible for memory and emotion. However, changes in hippocampus by UV irradiation to the skin have not been studied. In this study, after 2 weeks of UV irradiation to the mouse skin, we examined molecular changes related to cognitive functions in the hippocampus and activation of the hypothalamic-pituitary-adrenal (HPA) axis. UV exposure to the skin decreased doublecortin-positive immature neurons and synaptic proteins, including N-methyl-D-aspartate receptor 2 A and postsynaptic density protein-95, in the hippocampus. Moreover, we observed that UV irradiation to the skin down-regulated brain-derived neurotrophic factor expression and ERK signaling in the hippocampus, which are known to modulate neurogenesis and synaptic plasticity. The cutaneous and central HPA axes were activated by UV, which resulted in significant increases in serum levels of corticosterone. Subsequently, UV irradiation to the skin activated the glucocorticoid-signaling pathway in the hippocampal dentate gyrus. Interestingly, after 6 weeks of UV irradiation, mice showed depression-like behavior in the tail suspension test. Taken together, our data suggest that repeated UV exposure through the skin may negatively affect hippocampal neurogenesis and synaptic plasticity along with HPA axis activation.